The association of point-of-sale cigarette marketing with cravings to smoke: results from a cross-sectional population-based study. Issue 4 (29th May 2015) - Siahpush, Mohammad; Shaikh, Raees A; Cummings, K Michael; Hyland, Andrew; Dodd, Michael; Carlson, Les; Kessler, Asia Sikora; Meza, Jane; Wan, Neng; Wakefield, Melanie
Abstract : Objective: To examine the association between recalled exposure to point-of-sale (POS) cigarette marketing (ie, pack displays, advertisements and promotions such as discounts) and reported cravings to smoke while visiting a store. Methods: Data were collected using a telephone survey of a cross-sectional sample of 999 adult smokers in Omaha, Nebraska. Recalled exposure to POS cigarette marketing was measured by asking respondents about noticing (a) pack displays, (b) advertisements and (c) promotions in store in their neighbourhood. A 3-item scale indicating the frequency of experiencing cravings to smoke in locations where cigarettes are sold was created by asking respondents: (1) "feel a craving for a cigarette?" (2) "feel like nothing would be better than smoking a cigarette?" and (3) "feel like all you want is a cigarette?" The association between recalled exposure to POS cigarette marketing and cravings was estimated using ordinary least squares linear regression models, controlling for nicotine dependence, gender, age, race/ethnicity, income, education, frequency of visiting stores in one's neighbourhood and method of recruitment into the study. Results: Recalled exposure to POS cigarette displays (p<0.001) and advertisements (p=0.002), but not promotions (p=0.06), was associated with more frequent cravings to smoke. Conclusions: Recalled exposure to POS cigarette marketing is associated with cravings to smoke as predicted by laboratory studies on the effects of smoking cues on cigarette craving. Policies that reduce or eliminate POS cigarette marketing could reduce cigarette cravings and might attenuate impulse buying of cigarettes.